Question #bef4d

1 Answer
Sep 17, 2016

Answer:

#x=4"; "y=6#

Explanation:

Given:
#" "x=y-2#..................Equation(1)
#" "3x-y=6#...............Equation(2)
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(green)("Determine the value of "y)#

#color(purple)("Method shown in great detail")#

Substitute for #x# in equation(2) using equation(1)

#color(brown)(3x-y=6)color(blue)(" "->" "3(y-2)-y=6#

#3y-6-y=6#

#2y-6=6#

Add 6 to both sides

#2y-6+6=6+6#

#2y+0=12#

Divide both sides by 2

#2/2xx y=12/2#

#color(green)(y=6)#
'~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(green)("Determine the value of "x)#

Given that #y=6# equation(1) becomes:

#x=6-2" "........................Equation(1_a)#

#color(green)(x=4)#